Elaboration of the ether cleaving ability and selectivity of the classical pearlman's catalyst [Pd(OH)(2)/C]: concise synthesis of a precursor for a myo-inositol pyrophosphate - Mart, Alson; Shashidhar, Mysore S. (Tetrahedron, 2012)
The cleavage of propargyl, allyl, benzyl, and PMB ethers by Pd(OH)(2)/C can be tuned in that order, by varying the reaction conditions. Other moieties such as C-C double bonds, esters, trityl ether, p-bromo and p-nitrobenzyl ethers are stable to these reaction conditions. Cleavage of allyl ethers can be made catalytic by using 1:1 mixture of Pd(OH)(2)/C and Pd/C. The synthetic potential of the selective ether cleaving ability of Pd(OH)(2)/C, essentially under neutral conditions, has been demonstrated by an efficient synthesis of a precursor for the preparation of an inositol pyrophosphate derivative. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Ether cleavage; Inositol; Palladium; Protecting group

Palladium mediated selective cleavage of benzyl and allyl phosphates: a convenient non-hydrogenolytic method for the synthesis of phosphates and phospholipids. - Mart, Alson; Sarkar, Nitai N.; Shashidhar, Mysore S. (ChemistrySelect, 2022)
Palladium(II) hydroxide on carbon is a catalyst routinely used for the cleavage of O-benzyl groups by hydrogenolysis to obtain the corresponding parent organic compound. The work described in this article shows that allyl and benzyl phosphates, can be cleaved efficiently and selectively using palladium(II) hydroxide on carbon, under non-hydrogenolytic and neutral conditions, precluding the migration of acyl groups. The utility of these cleavage reactions for the synthesis of diacylglycerol and phosphatidic acid, containing unsaturation, is demonstrated. These methods have high potential for the synthesis of a variety of phosphates and natural phospholipids.
Keywords: Carbohydrate; Ether cleavage; Palladium; Phosphate; Phospholipid; Protecting group